E-governance a global perspective on a new paradigm (Washington, DC IOS Press, 2007)
e-Governance is regarded as one of the most important subjects in the Information Society. Global e-governance for both public and private sectors is becoming extremely significant in an innovative and seamless world community. Waseda University Institute of e-Government, founded in 2001, is a pioneer for capacity-building on CIO training and human resource development as well as international ranking on e-government activities. It has also played an important role of regional ICT cooperation in APEC region as APEC e-Government Research Center. This publication is divided into five parts: Information/Ubiquitous Society offers understanding of what information society or ubiquitous society is all about. e-Government deals with different countries/areas in the world focusing on all of their visions, strategies and priority areas as well as on the key challenges and lessons of e-Government. The selection covered (Japan, China, Thailand, USA, Brazil, Indonesia, Russia and Taiwan) gives a fair reflection of different e-Government scenarios. The third subject is e-Municipality and focuses on several key areas - some services, infrastructures and practices. In ICT and Applications several applications in the field of ICT including broadband and disaster issues are introduced and highlighted. The Role of CIO shows that CIO (Chief Information Officer) is at present the most attractive post within organizations at the stage of Information Society. This publication contains the views of various authors with a profound experience in global e-Governance. The quality of this book was ensured by the exemplary editorial efforts of the brilliant researchers at Waseda University Institute of e-Government.
"International Conference on Global e-Governance."--P. v.
Keywords: Internet in public administration--Congresses.